DAMPAK PEMBANGUNAN BENDUNGAN BENER PADA PEREKONOMIAN PROVINSI JAWA TENGAH: PENDEKATAN ANALISIS INPUT-OUTPUT - Sabila, Ghaisa Adani; Suharto, Umayatu Suiroh; Syaifudin, Rizal; Ginanjar, Rah Adi F. (LP2M Universitas Bina Bangsa, 2025)
The construction of the Bener Dam in Central Java Province is one of the National Strategic Projects that has been funded by the government and carried out development. This study identifies the conditions of interconnection between economic sectors in Central Java Province, the leading sector of Central Java Province, and identifies the impact of the Bener Dam Construction that occurred in 2023 on the economic condition of Central Java Province. The main data in this analysis is the Input-Output Table of Central Java Province Domestic Transactions on the Basis of Producer Prices (17 Business Fields), 2016 (Million Rupiah). The analysis method used is the General Balance analysis method. The results of the analysis explain that the economy of the Central Java region shows the condition of inter-sector linkages. This analysis can also identify the leading sectors of the Central Java region. Meanwhile, the results of the impact analysis on sectoral output changes showed that the largest sectoral output change was the processing industry sector by 0.61 percent, the sectoral output change was followed by the construction sector, the large trade and retail sectors; car and motorcycle repair, agriculture, forestry and fisheries sectors as well as the provision of accommodation and food and drink. Meanwhile, for the results of the total output change, a change value of 0.16 percent was obtained